A full treatment of peculiar velocities on the reionization light cone. Issue 1 (26th September 2019) - Chapman, Emma; Santos, Mario G
ABSTRACT: Accurate simulations of the 21-cm signal from the Epoch of Reionization require the generation of maps at specific frequencies given the values of astrophysical and cosmological parameters. The peculiar velocities of the hydrogen atoms producing the 21-cm radiation result in a shift in the observed frequency of the 21-cm radiation and changes the amplitude of the signal itself. This is not an effect we can remove but instead needs to be accurately modelled to ensure we infer the correct physical parameters from an observation. We describe the full calculation of the distortion of the 21-cm signal, and propose a new code that integrates the 21-cm intensity along the line of sight for each individual light cone pixel to fully capture the intensity contributions from multiple redshifts. This algorithm naturally deals with the typical divergences found in standard approaches, allowing for large optical depths and 21-cm absorption events at high redshifts. We find the new method results in up to a 60 per cent decrease in power on the largest scales on the sky, and an increase of over 80 per cent on the smallest scales on the sky. We find that the new implementation of the light cone results in a longer tail of bright temperatures in the brightness temperature distribution, as a result of the successful circumventing of a previous cap that had to be implemented to avoid a divergence in the brightness temperature. We conclude that this full treatment of the evolution of the light cone pixel can be an important effect.